The Impact of Religious and Ethnic Diversity on Business and Public Policies Strategies - Iustin Cornel Petre; Kamer-Ainur Aivaz (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
The present study, based on data provided by the National Institute of Statistics on the ethnic and religious distribution of the population in Romania, analyzes the main ethnic groups in our country: Romanians, Hungarians, Roma, Germans and Ukrainians and their religious affinities in relation to the main Christian denominations: Orthodox, Roman Catholic, Greek Catholic, Reformed, Pentecostal, Baptist and Adventist. Using factorial correspondence analysis (FCA), the study revealed the linkages and distribution of each ethnic group within the seven denominations analyzed. A significant relationship was found between Romanians and the Orthodox Church, Hungarians and the Roman Catholic and Reformed Churches, Roma and the Pentecostal Church, Germans and the Roman Catholic Church, and Ukrainians and the Adventist Church. The conclusion of the study is that governmental public policies and organizational leadership must consider these affinities of each ethnic group in relation to the specific moralities of the various denominations if they seek to achieve business success or multicultural harmonization and social inclusion.